The Impact of The Flipped Classroom ‎on Conceptual Understanding Toward ‎Students’ Different Learning Styles - Muktiadji, Henky; Degeng, I Nyoman Sudana; Setyosari, Punaji; Kuswandi, Dedi (International Journal of Basic and Applied Sciences, 2025)
This study investigates the effectiveness of the flipped classroom model in enhancing students’ conceptual understanding in ‎mathematics, with a focus on visual and auditory learning styles. The flipped classroom, which shifts direct instruction to ‎individual study and reserves class time for active engagement, offers a promising alternative. A two-part instrument was used ‎to assess students’ learning styles and their conceptual understanding in mathematics. Findings indicate that both the flipped ‎classroom strategy and students’ learning styles significantly influence achievement. However, the interaction between the two ‎was not statistically significant, suggesting that each factor contributes independently to learning outcomes. These results ‎highlight the importance of designing inclusive instructional strategies that support varied learning preferences without ‎requiring strict alignment. The study recommends further exploration of kinesthetic learners, long-term impacts of flipped ‎instruction, and the role of specific media types in supporting different learning styles across broader educational contexts.
Keywords: Flipped Classroom; Mathematical Concept Understanding; Learning Styles